Development and Validation of a Novel Reversed Phase High Performance Liquid Chromatography with Refractive Index Detector Method for Assay of Polyvinyl Alcohol in an Ophthalmic Solution - Ergen, Harun; Guleli, Muge; Sener, Cigdem; Caliskan, Cem; Semiz, Sercan; Ozbek, Mahmut (Current Pharmaceutical Analysis, 2020)
Introduction: Polyvinyl alcohol (PVA), a polymer, is in demand due to its usage in different applications such as pharmaceutical, biomedical and textile, paper, food industries. Methods: A new sensitive reversed phased high-pressure liquid chromatography (RP-HPLC) method with refractive index detector (RID) was developed for determination of PVA in an ophthalmic solution containing dexpanthenol and PVA as active substances and it was validated according to The International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) guideline. Results: Chromatographic separation was achieved on a Chiral-AGP (150 mm × 4.0 mm, 5 μm) column kept at 30°C with an isocratic flow at a flow rate of 1.0 ml/min. The detector temperature was 30°C, the retention time of PVA was around 1.0 min and the total run time was 5 minutes. Conclusion: The proposed method showed linearity, accuracy, precision, specificity, robustness, solution stability, and system suitability results within the acceptance criteria.
Keywords: RP-HPLC